2013
DOI: 10.1021/jo402387t
|View full text |Cite
|
Sign up to set email alerts
|

Oxazoline and Imidazoline Functionalization of a C60 Dimer via the Reaction of C60HBn and Aromatic Nitriles with a Bifunctional Hydroxide

Abstract: Oxazoline and imidazoline functionalization of a singly bonded C60 dimer is achieved via a one-pot reaction of C60HBn with OH(-) and aromatic nitriles, where the OH(-) not only functions as a Brønsted base that deprotonates C60HBn but also as a nucleophile that initiates the nucleophilic addition to the fullerene cage. The structures of the obtained oxazolinated and imidazolinated C60 dimeric compounds have been established by HRMS, UV-vis, and (1)H, (13)C, and HMBC NMR characterizations and computational calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…The covalent bond that directly connects the two C 60 cages is weak and easily cleaved, , consistent with the elongated bond length (1.576–1.645 Å) − , compared with the typical C–C bond length (1.541 Å) . In addition, the 1,4-positioned addends in the 1,4–1′,4′-RC 60 –C 60 R dimers may act as the directing groups in controlling the reaction site for the subsequent nucleophilic addition with the formation of a stable type of 1,4,15-R 3 C 60 – intermediate bearing the 10π indenyl anion resonance structure, similar to the cases of 1,4-R 2 C 60 derivatives, , making 1,4–1′,4′-RC 60 –C 60 R an interesting starting material for fullerene functionalization. Here, we report the methoxylation of 1,4–1′,4′-BnC 60 –C 60 Bn ( 3 , Scheme ), which exhibits different regiocontrol compared with that of functionalizing C 60 directly.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The covalent bond that directly connects the two C 60 cages is weak and easily cleaved, , consistent with the elongated bond length (1.576–1.645 Å) − , compared with the typical C–C bond length (1.541 Å) . In addition, the 1,4-positioned addends in the 1,4–1′,4′-RC 60 –C 60 R dimers may act as the directing groups in controlling the reaction site for the subsequent nucleophilic addition with the formation of a stable type of 1,4,15-R 3 C 60 – intermediate bearing the 10π indenyl anion resonance structure, similar to the cases of 1,4-R 2 C 60 derivatives, , making 1,4–1′,4′-RC 60 –C 60 R an interesting starting material for fullerene functionalization. Here, we report the methoxylation of 1,4–1′,4′-BnC 60 –C 60 Bn ( 3 , Scheme ), which exhibits different regiocontrol compared with that of functionalizing C 60 directly.…”
mentioning
confidence: 92%
“…Considering that 1,4,15-R 3 C 60 – monoanionic intermediate with the 10π indenyl resonance subunit is typically formed when 1,4-R 2 C 60 is subjected to nucleophilic addition, , it is rational to assume that anionic intermediate A with the 1,4,15-configuration (Figure ) is formed via the methoxylation of 3 , where the methoxy is positioned at the para site with respect to the benzyl group judging from the structure of 2 . Figure a shows the optimized structure of intermediate A , and Figure b shows the HOMO distribution of the intermediate obtained with Gaussian09 at the B3LYP/3-21G level.…”
mentioning
confidence: 99%
“…We have recently reported the synthesis of singly bonded C 60 dimers with a 1,2,4,15-configuration that bear an oxazoline or imidazoline heterocycle on one of the carbon cages and one benzyl (Bn) group on each individual C 60 cage (compounds 1 and 2 in Figure ) . These dimeric molecules are subjected to reductive cleavage of the C 60 –C 60 bond, , generating monomeric tris-organo[60]­fullerene monoanions bearing a heterocycle with a 1,2,4-configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on multiple nucleophilic additions to C 60 and C 70 has shown that electronic factors such as the electrophilic Fukui functions f k + , , NBO charge distribution, and LUMO composition analysis of the 1-fold addition adducts are important in understanding the regioselectivity of the 2-fold nucleophilic addition reactions. Calculations on the electrophilic Fukui functions f k + , NBO charge distribution, and LUMO composition of 1-Bn-2-MeOC 70 ( 2 ) and 2-MeO-5-BnC 70 ( 4 ) were performed to study the regioselectivity of the reaction, which all predicted a similar result in that compound 6 was more feasible to form over the 2 and 12 o’clock isomers as the respective carbon atom was more electrophilic compared with the counterparts.…”
Section: Resultsmentioning
confidence: 82%